Assessment of competence of steel furnace staff in computer simulator project - Колесникова, Екатерина Викторовна (Eastern-European Journal of Enterprise Technologies, 2013)
The paper gives the analysis of interaction between the parties interested in the steelmaking project, which includes two possible cycles of competence increasing. The first cycle deals with working at the real object and possible damage in case of staff error. The second cycle does not concern the external and internal environment of the project and is executed on a computer simulator, which, of course, can not lead to damage. The proposed method for determining the level of staff competence is based on the fact that success of the steelmaking project corresponds to the competence level. For an overall assessment of staff competence it is necessary to divide the steelmaking project into operations, which assessment is performed on the basis of process regulations. Using the proposed method for assessing the staff competence will allow solving the existing contradiction between the requirements of efficiency of steelmaking projects management and the staff competence level.